TEKNIK PEMANENAN MADU LEBAH HUTAN OLEH MASYARAKAT SEKITAR HUTAN DI KECAMATAN MALLAWA KABUPATEN MAROS - Mujetahid, A. (PERENNIAL, 2008)
This research purpose to understand the technique of forest honey bee harvesting and income of local community who harvest the honey of forest honey bee in District of Mallawa, Regency of Maros. Data was obtained through observation, intervieuw and discussion method to the related stakeholders and collected by using purpossive sampling method. The number of respondents involved in this research were 30 persons. Data that have been collected then calculated, tabulated and descriptively analyzed according to research objective. The result of research shows that technique of forest honeybee harvesting consists of several steps. The first step was preparation of harvesting tools such as amung used for smoking the honey comb, kondre for putting the honey comb in container and stain for climbing the tree. The next steps were climbing the tree, taking and sorting the honey comb from the tree, putting down the honey comb, compressing the honey comb and packing the honey. Harvest yield of honey was 1,601,25 kg/year or Rp 28,200,000/year or the average was Rp. 940,000/year. Key words: Technique harvesting, honey bee, local community around the forest area, income